Subcritical water extraction of total phenolic compounds from Piper betle L. leaves: effect of process conditions and characterization - Rahmah, Nur Lailatul; Mustapa Kamal, Siti Mazlina; Sulaiman, Alifdalino; Taip, Farah Saleena; Siajam, Shamsul Izhar (Springer, 2023)
Subcritical water extraction (SWE) as a green separation technology becomes a suitable choice to recover the phenolic compounds of Piper betle L. (PBL) leaves. This experiment utilized subcritical water using a batch fluid extraction system with two factors of process conditions: temperature ranging from 100 to 275 °C and time from 5 to 30 min. Positive interaction effect (p < 0.05) between temperature and time for total phenolic content (TPC) and antioxidant activity (AA) were obtained from the two-way analysis of variance. The highest TPC (7.89 ± 0.26 mg GAE/g) and AA (92.98 ± 1.79%) were obtained by subcritical water at the operation conditions of 200 °C, 1.55 MPa, 15% solid loading for 5 min. The functional groups detected from infra-red spectra analysis were presumably the phenolic compound’s structure. Scanning electron microscope showed pores formation in the residue of PBL leaves after treated by SWE. The best extract of PBL leaves recovered from the SWE process inhibited the proliferation of the SW-480 (human colorectal adenocarcinoma) cell with IC50 value of 100 µg/mL. Hence, these findings enhance the understanding of SWE as a good alternative method for separating phenolic compounds from PBL leaves, and the best extract was potentially applicable as an anticancer treatment.